Physical frailty and decline in general and specific cognitive abilities: the Lothian Birth Cohort 1936. Issue 2 (5th November 2019) - Gale, Catharine; Ritchie, Stuart J; Starr, John M; Deary, Ian J
Abstract : Background: Physical frailty is associated with many adverse outcomes including disability, chronic disease, hospitalisation, institutionalisation and death. It is unclear what impact it might have on the rate of normal cognitive ageing. We investigated whether physical frailty was related to initial level of, and change in, cognitive abilities from age 70 to 79 years. Method: Participants were 950 members of the Lothian Birth Cohort 1936. Physical frailty was assessed at age 70 years using the Fried criteria. Cognitive function was assessed at ages 70, 73, 76 and 79 years. We used linear regression to examine cross-sectional and prospective associations between physical frailty status at age 70 years and factor score estimates for baseline level of and change in four cognitive domains (visuospatial ability, memory, processing speed and crystallised ability) and in general cognitive ability. Results: Physical frailty, but not prefrailty, was associated with lower baseline levels of visuospatial ability, memory, processing speed and general cognitive ability after control for age, sex, education, depressive symptoms, smoking and number of chronic illnesses. Physical frailty was associated with greater decline in each cognitive domain: age-adjusted and sex-adjusted standardised regression coefficients (95% CIs) were: −0.45 (−0.70 to –0.20) for visuospatial ability, −0.32 (−0.56 to –0.07) for memory, −0.47 (−0.72 to −0.22) for processing speed, −0.43 (−0.68 to –0.18) for crystallised ability and −0.45 (−0.70 to –0.21) for general cognitive ability. These associations were only slightly attenuated after additional control for other covariates. Conclusion: Physical frailty may be an important indicator of age-related decline across multiple cognitive domains.